It's one of us [large type] - Ellison, J. T. (Thorndike Press large print basic series, 2023)
"Olivia Bender desperately wants to be a mother. Fertility treatments keep failing. And just when she feels she's at her lowest point, the police deliver shocking news to Olivia and her husband, Park. DNA results show that the prime suspect in a murder investigation is Park's son. Olivia is relieved, knowing the Benders don't have any children. Then comes the confession. Many years ago, Park donated sperm to a clinic. As the murder investigation goes deeper, more truths come to light. With every revelation, Olivia must face the unthinkable. The man she married has fathered a killer. But can she hold that against him when she keeps such dark secrets of her own?"--